Muslim and Power in China: Uyghur Muslim Upheaval, Nationalism and Their Diaspora in International Arena - Sahrasad, Herdi; Chaidar, Al; Tabrani, Dedy; Hasan, Pipip A. Rifai (Jurnal Review Politik, 2024)
The Uyghur Muslims of Xinjiang, People's Republic of China, suffered under the communist rule of Mao Zedong, Deng Xiaoping, Zhu Rongji, and Xi Jinping for decades. Thankfully, most people don't know about this. Uyghur Muslims continue to endure allegations and stigmatization for standing up to China's lengthy history of oppression and massacre. Unfortunately, there is less international compassion for the Uyghur crisis. This paper uses a descriptive-analytical qualitative technique based on data obtained from interviews, documents, and library studies to track the upheaval among Uyghur Muslims as it progresses from terrorist activities to concerns about nationalism. As a result of their tragic situation, thousands of Uyghur Muslims have fled to neighboring countries in search of humanitarian solutions; they are currently residing in diaspora in places like Turkey, Afghanistan, Tajikistan, the Middle East, Southeast Asia, and so on. As a result of their terrible situation in China, thousands of Uyghur Muslims have fled to diasporas in that places, in search of humanitarian answers without certainty of their future.